Free Tissue Reconstruction of the Scalp - Sokoya, Mofiyinfolu; Misch, Emily; Vincent, Aurora; Wang, Weitao; Kadakia, Sameep; Ducic, Yadranko; Smith, Jesse (Seminars in Plastic Surgery, 2019)
Reconstruction of scalp defects can be accomplished by many methods, but larger defects, especially those in which the periosteum is absent or calvarial defects are present, require free tissue transfer. Various methods of scalp reconstruction, as guided by the defect components and size, are presented herein, with a focus on free tissue transfer. Different free flaps for scalp reconstructed are described with a comparison of their advantages and disadvantages. Overall, free tissue transfer for scalp defects provides a reliable, durable, and cosmetically adequate reconstructive option.
Keywords: scalp; free flap; reconstruction